The Effect of Gender Stereotypes on the Entrepreneurial Creative Process of Divergent Thinking - Williams, Layo / L.W (2013)
Previous research has shown that the activation of stereotypes on women’s math performance impinged their mathematical abilities causing them to do worse than their abilities. However, this research has not been carried out or applied in the creativity domain. So this article linking the concepts of gender, creativity and entrepreneurship investigated the effect of gender stereotypes on the entrepreneurial creative process of divergent thinking. This research relied on an experiment that entailed the participation of 36 women, stereotype activation and the completion of a divergent thinking task. The Guilford Alternative Uses task was given to two groups – an experiment group subjected to implicit stereotype activation and a control group that only completed the divergent thinking task. The results of the research showed no significant difference in the scores of the two groups which suggests that unlike the results of the previous research, gender priming has no effect on the creative ability of women.